Endocannabinoid system in cardiovascular disorders - new pharmacotherapeutic opportunities - Pedro Cunha; Ana M Romão; Filipa Mascarenhas-Melo; Helena M Teixeira; Flávio Reis (Wolters Kluwer Medknow Publications, 2011)
The long history of Cannabis sativa had its development stimulated and oriented for medicine after the discovery and chemical characterization of its main active ingredient, the 9-tetrahydrocannabinol (9-THC). Consequently, a binding site for 9-THC was identified in rat brains and the first cannabinoid receptor (CB1) was cloned, followed by the CB2 and by the discover of two endogenous agonists: anandamide and 2-arachidonoyl glycerol. Cannabinoid receptors, endocannabinoids and the enzymes that catalyze its synthesis and degradation constitute the endocannabinoid system (ECS), which plays an important role in the cardiovascular system. In vivo experiments with rats have demonstrated the action of anandamide and 2-AG on the development of atherosclerotic plaque, as well as an effect on heart rate, blood pressure, vasoactivity and energy metabolism (action in dyslipidemia and obesity). Recent studies with an antagonist of CB1 receptors showed that the modulation of ECS can play an important role in reducing cardiovascular risk in obese and dyslipidemic patients. Similarly, studies in rats have demonstrated the action of CB2 receptors in adhesion, migration, proliferation and function of immune cells involved in the atherosclerotic plaque formation process. The evidence so far gathered shows that the modulation of ECS (as agonism or antagonism of its receptors) is an enormous potential field for research and intervention in multiple areas of human pathophysiology. The development of selective drugs for the CB1 and CB2 receptors may open a door to new therapeutic regimens.This review article aims to address the key findings and evidences on the modulation of ECS, in order to prospect future forms of therapeutic intervention at the cardiovascular level. A recent, emerging, controversial and of undoubted scientific interest subject, which states as a potential therapeutic target to reach in the 21 st century.